2021
DOI: 10.1016/j.diabres.2021.109025
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of thioredoxin contributes to inhibiting diabetic hearing impairment

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Boosting lysosomal cathepsin D activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function [40]. The expressions of PINK1, Parkin and cathepsin D were related with Trx-1 expression in diabetic diseases and AD [42][43][44]. The decreased expression of cathepsin D by MPTP was restored in Trx-1 overexpressing mice and further decreased in Trx-1 knockdown mice (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Boosting lysosomal cathepsin D activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function [40]. The expressions of PINK1, Parkin and cathepsin D were related with Trx-1 expression in diabetic diseases and AD [42][43][44]. The decreased expression of cathepsin D by MPTP was restored in Trx-1 overexpressing mice and further decreased in Trx-1 knockdown mice (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…A study by Ren et al identified the protective effect of Thioredoxin (Trx) on DM-induced SNHL and to identify an early potential therapeutic target for diabetic hearing impairment in the future [ 60 ]. Thioredoxin (Trx) is a small redox protein present in tissues which contains dithiol-disulfide active site, which functions to regulate oxidative stress [ 61 ], endoplasmic reticulum stress [ 62 ], and autophagy in biological processes [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ren et al demonstrated that elevating Trx levels with sulforaphane reduces DM-related cochlear hair cell damage [ 60 ]. Trx, known for its role in reducing apoptosis and supporting cell metabolism [ 71 ]., helps mitigate cochlear degeneration in DM by influencing mitochondrial function and reducing ER stress and autophagy.…”
Section: Discussionmentioning
confidence: 99%